Implantação de um sistema de planejamento e controle de manutenção utilizando a ferramenta WCM no setor industrial - Maciel, Jocasta Oliveira (2019)
The current market is increasingly demanding in relation to the quality of products and services offered and industry competitiveness is high. This makes the proper functioning of the machines and equipment are fundamental for the pursuit of excellence of the productive process, for this reason the reliability and efficiency of the machines must be guaranteed. In this way, good planning and maintenance control makes all the difference in the industrial sector. Therefore, the objective of this work is to create effective corrective maintenance planning using WCM (World Class Manufacturing) and TPM (Total Productive Maintenance) tools to contribute to the continuous improvement of the maintenance and to improve the reliability of the machines. For this, has developed the planning with the bibliographic study, data collection, programming, implementation and results. In addition, the planning of notifications of the autonomous maintenance was implemented, aiming at a better control of the indicators of the autonomous pillar. The results obtained with the implementation of the plans were satisfactory and contributed to the improvement of the performance indicators of the machines in the year 2017, also helped in the better distribution of maintenance orders and in the control of materials and costs of the area.